The Relationship Between Earnings Management and Firm Performance in the Companies Listed in Tehran Stock Exchange: The Function of Firm Size - Simin Mojoodiniay Kasmaei; Mohammad Javad Tasaddi Kari (Environmental Energy and Economic Research, 2023)
In the process of earnings management, the financial reports are changed in order to misguide shareholders about the firm basic performance, or to affect the contractual outcomes associated with reported accounting numbers, which can be positive or negative for firm performance under some conditions. In the present study, it was aimed to determine the relationship between earnings management and firm performance. The research population included the present listed companies on the Tehran Stock Exchange during 2013-2018. After screening, data related to 105 companies were analyzed through panel approach. No remarkable relationship was discovered between earnings management and firm performance based on the obtained results. Moreover, firm size indicated a significant relationship with performance. It seems that in the conditions of financial crisis and the instability of economic structures, some managers were interested in earnings management, which was implemented through various approaches in the firm ultimately affecting its performance. However, such an effect was not significant in the current study.